FINANCIAL INTEGRATION, KNOWLEDGE SHARING AND ECONOMIC GROWTH: DOES THE EXPERIENCE OF DEVELOPING COUNTRIES DIFFER FROM DEVELOPED COUNTRIES? - Ghulam Shabeer, Muhammad (The journal of contemporary issues in business and government, 2022)
Economic growth is still a central macroeconomic goal of every society, whether rich or poor and this study has explored the role of financial integration and knowledge sharing in this regard by assuming that their effect on the economic growth of developing and developed countries may be different. This study has chosen the country classification made by the United Nation’s WESP classification. Feasible generalized least square (FGLS -hetero) approach is used for estimation from a data set of 1995 to 2019 and the results show that financial integration has a positive impact on the economic growth of developed nations but has a negative impact on the economic growth of developing economies. Knowledge sharing, research and development expenditure, institutions, interpersonal globalization have a positive impact on the economic growth of developing and developed economies.